Educação financeira no contexto do ensino médio: contribuições e perspectivas - OLIVEIRA, Josué Rodrigues de (2022)
Financial Education or Financial Literacy is a topic that has gained prominence in academic environments and schools in recent years. Thus, this research has as main objective to investigate the level/profile of Financial Education of students in the 1 in High School and the contributions of Mathematics classes to their Financial Literacy. The theoretical discussion that supported the construction of this work was based mainly on Meneghetti Neto; Falcetta; Rassier; Marchionatti; among others. The research is qualitative and exploratory. The context of the investigation is a public high school and the participants are students who were in the 1st year in 2019. They were chosen according to criteria related to age, whether or not to exercise labor activity and availability to participate in the research. A questionnaire composed of 10 questions was applied, in December 2019, to build information about the following aspects, age, employment, consumer profile and indebtedness. The Mathematics II teacher, a discipline with an emphasis on financial mathematics, allowed the interview with the students, as long as the answers could serve as a parameter for planning the discipline for the next school year. The survey showed that many students are not in the job market, have different consumer profiles, accumulate debt and recognize the importance of math classes to face everyday situations related to purchases and sales.